Desenvolvimento e implementação de modelos de cálculo para análise térmica microclimática em ambiente SIG - Favretto, Ana Paula Oliveira (2021)
The urbanization impact over the microclimate highlights the importance of using climatological criteria to guide urban planning. The advent and development of Geographic Information System (GIS) plays an important role in climate guided urban planning breakthroughs, as it allows data layering and predictive analyses. A calculation model to automate the Frontal Area Index (FAI) and Thermal Potential Index (TPI) mapping, and the prediction of wind and cooling routes based on Least Cost Path analyses over the generated maps is developed and implemented in this research. The calculation model is implemented as a group of Python Script Tools embedded in ESRI© ArcGIS Pro 2.7.0. For that we used the ArcPy Python Library, which allows to access ArcGIS geoprocessing functions. A detailed description of the calculation model is presented and can be used to implement tools in other GIS platforms. The generated Script Tools are easy to use and its results allow the urban morphology assessment and also the study of its influence over wind route patterns. In this way, this research contributes both to advance of the Urban Climatology scientific field and to guide urban planner’s practical decision making.